2015
DOI: 10.3923/jps.2015.210.221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on Growth Parameters, Moisture Content, Relative Water Content and Photosynthetic Pigments of Fenugreek Variety RMt-1

Abstract: Present research was carried out with the aim of identifying effect of salt stress (NaCl 0.0, 50, 100, 150 and 200 mM) on growth and physiological parameters of fenugreek (Trigonella foenum-graecum L.) variety RMt-1, a leafy vegetable. Various parameters such as germination percentage, shoot and root length, shoot-root ratio, number of leaves and branches, vigour index, fresh and dry weight, moisture content, relative water content and photosynthetic pigments were analyzed. All the parameters were recorded at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 15 publications
5
11
0
Order By: Relevance
“…The moisture content of the studied 2-and 5-day old seedlings increased under most of the applied NaCl concentrations. A similar increase in moisture content of fenugreek plants at successive growth stages under salt treatment was lately recorded by Kapoor and Pande [28] who ascribed that pattern of change in moisture content to the deteriorative status of the plant cells under stress.…”
Section: Discussionsupporting
confidence: 79%
“…The moisture content of the studied 2-and 5-day old seedlings increased under most of the applied NaCl concentrations. A similar increase in moisture content of fenugreek plants at successive growth stages under salt treatment was lately recorded by Kapoor and Pande [28] who ascribed that pattern of change in moisture content to the deteriorative status of the plant cells under stress.…”
Section: Discussionsupporting
confidence: 79%
“…The observed decrease in leaf number and FW in moderate and high salinity levels is attributed to a reduction in cell expansion due to low turgor controlled by cellular water uptake and cell-wall extension 42 . In addition, Kapoor and Pande 43 concluded that leaf numbers decreased under salinity conditions due to a reduction in branches per plant as a result of decrease in nutrient concentrations. Decline in fresh and dry weights, leaf numbers and abscissions under salinity stress were previously reported 44 .…”
Section: Resultsmentioning
confidence: 99%
“…As indicated by the table, although the receivers were not directly exposed to the salt stress, their dry and fresh weights were still reduced compared to the controls. Salinity has been associated with lowering of both fresh and dry weights and it is inversely proportional to the salt concentration [17,18,19].…”
Section: Discussionmentioning
confidence: 99%